Does News Platform Matter? Comparing Online Journalistic Role Performance to Newspaper, Radio, and Television (2023)
The shifting role of journalism in a digital age has affected long-standing journalistic norms across media platforms. This has reinvigorated discussion on how work in online newsrooms compares to other platforms that differ in media affordances and forms. Still, more studies are needed on whether those differences translate into distinct practices, especially when examining cross-national studies. Based on a content analysis of 148,474 stories produced by 365 media organizations from 37 countries, this article compares the performance of journalistic roles in online newsrooms to three other types of media—TV, radio, and print. The paper analyzes if journalistic roles present themselves differently across platforms, and if these differences are constant or they vary across countries. Results show that there are measurable differences in role performance in online journalism compared to other platforms. Platform had a significant impact, particularly in terms of service and infotainment orientation, while the implementation of roles oriented toward public service was more similar. Additionally, country differences in the relationship between role performance and platforms mainly emerged for roles that enable political influence on news coverage, with differences in the relationship between online vs. traditional platforms appearing to be distinct features of the specific political system. © 2023 Informa UK Limited, trading as Taylor & Francis Group.